Niche Expansion Has Increased the Risk of Leptocybe invasa Fisher Et LaSalle Invasions at the Global Scale - Xianheng Ouyang; Jiangling Pan; Hui Rao; Qiaoyun Sun (Insects)
Invasive alien species often undergo shifts in their ecological niches when they establish themselves in environments that differ from their native habitats. Leptocybe invasa Fisher et LaSalle (Hymenoptera: Eulophidae), specifically, has caused huge economic losses to Eucalyptus trees in Australia. The global spread of eucalyptus cultivation has allowed L. invasa to threaten plantations beyond its native habitat. It is, therefore, urgent to implement effective control measures to mitigate the impact of this pest. The optimized MaxEnt model was used to predict the potential global distribution of L. invasa based on occurrence data and environmental variables. The centroid shift, overlap, unfilling, and expansion (COUE) framework was employed to evaluate niche dynamics during the global invasion process by comparing the ecological niches of L. invasa in both native regions and regions affected by invasions (hereafter referred to as “invaded”). The results indicated that the distribution of L. invasa is primarily influenced by temperature, precipitation, and the human influence index variables. Its ecological niche was shown to have considerably expanded from native to invaded regions. Under future climate scenarios, the potential geographical distribution of L. invasa is projected to be concentrated primarily in East Asia, Southeast Asia, Western Europe, and Southern Oceania. In the future, the potentially suitable areas for the establishment of L. invasa are expected to further expand. This study provides a unified framework for exploring the niche dynamics of invasive alien species globally. Emphasizing early warning and control in uninvaded areas is crucial for minimizing L. invasa ecological and economic threats.